A comparative study on CdS: PEO and CdS: PMMA nanocomposite solid films. (August 2016) - Padmaja, S.; Jayakumar, S.; Balaji, R.; Vaideki, K.
Graphical abstract: Abstract: Cadmium Sulphide (CdS) nanoparticles were reinforced in Poly(ethylene Oxide) (PEO) and Poly(methyl methacrylate) (PMMA) matrices by in situ technique. The presence of CdS in PEO and PMMA matrix was confirmed using X-ray photoelectron spectroscopy (XPS). Fourier Transform Infrared spectroscopy (FTIR) analysis disclosed the co-ordination of CdS in the matrices. Thermal analysis of the nanocomposites was carried out using Differential Scanning calorimetric studies (DSC). The optical studies using UV–vis spectroscopy were carried out to find the band gap of the materials and the absorption onset. The CdS particle size in the matrices was found by Effective Mass Approximation (EMA) model using the band gap values and was confirmed by TEM studies. The surface trapped emissions of the nanocomposites were observed from the photoluminescence (PL) spectra. The distribution of CdS particles in the polymer matrices were presented by Atomic force microscopic studies (AFM).